Challenges and Readiness of Public Organizations in Electronic-Based Services: A Study at the Medan City Land Office - Anzar Abidin Nadjpa; Sawitri Budi Utami; Pardamean Daulay (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study will discuss and analyze the challenges and readiness of government or public organizations in implementing an electronically integrated mortgage service (HT-el) policy implemented by the Medan City Land Office. The basic question in this study is how the challenges and readiness of resources, organizational units and the use of methods in implementing an electronically integrated mortgage service (HT-el) policy are. In order to examine this topic, the theory of policy implementation by Charles O. Jones (1984) will be used as an analytical knife. This study finds that resource support, especially human resources, is a challenge for organizations considering that the transformation of service methods from conventional forms to electronic-based services requires a certain capacity, expertise and creativity in addition to the quantity of resources to ensure that the application for HT-el issuance can be served. To ensure that HT-el services are carried out perfectly, the Land Office has carried out bureaucratic reforms, either through the determination of certain functional positions based on expertise, institutionalization of ethics and the establishment of Service Integrity Zones.